Strategisk och taktisk planering samt länken där emellan : analys av planeringsprocessens genomförande vid SCA Skog - Eriksson, Malin (SLU/Dept. of Forest Resource Management, 2008)
To effectively manage a forest resource for both economic and other values good planning is required. The problem is complex since you want to know which forest to cut and when. Often a hierarchical planning structure is applied, including strategic (long-term), tactical, (medium-term) and operational level. Today SCA Forest is one of few forestry companies in the northern Sweden with an integrated forest wood supply and industry. The goals of the company are to supply their own industries with wood and to manage the resources of the forest through a long-term perspective with satisfactory profitability. SCA tries to meet these objectives by doing long-term forecasts of timber yield and transferring the results from these in the subsequent planning process. The goals of this work were to: • Evaluate how SCA Forest do their long-term forecast of timber yield. Which advantages and disadvantages are there with this approach? • Evaluate which tools and selection rules are being used to transfer the results from the long-term forecast of timber yield into tactical planning from staff- to administration and district level. • Pinpoint possible problems in the processes above and suggest solutions. For the descriptive study a qualitative method was used. I first collected information through literature studies and interviews with employees at SCA, and thereafter processed the material. Today SCA Forest uses the Forest Management Planning Package to perform their long-term forecast of timber yield in their strategic planning. Using this system you follow a certain work process including definition of objectives, inventory of the forest, projections of forest development, optimization, and then linking the strategic results to the tactical planning. Some weaknesses of the system are that other aspects than timber production and spatial problems cannot be handled. A new management and planning system, Heureka, is being developed at SLU with which it should be possible to analyze several different aspects simultaneously. ...